Finite-element analysis of residual stresses in the TC4 titanium alloy treated by laser shock peening - Plekhov, Oleg Anatol’yevich; Kostina, Anastasiya Andreyevna; Iziumov, Roman Igorevich; Iziumova, Anastasiya Yur’yevna (Computational Continuum Mechanics, 2022)
Laser shock peening is an effective tool for generating deep compressive residual stresses (more than 1 mm) near the surface of metallic structures. This can improve their mechanical properties and fatigue performance. For this purpose, it is necessary to find optimal laser shock parameters. In this paper, the effect of laser intensity and peening pattern on the residual stress field in a Ti-6Al-4V titanium alloy is investigated through numerical simulations. The applied approach includes two steps. In the first stage, the modeling of elasto-plastic stress waves is performed. The second stage involves a solution of static equilibrium problem for residual stress distribution taking into account plastic deformation fields. The analysis was carried out for a square plate with a thickness of 3 mm, the central part of which is subjected to a series of square laser pulses. The pulse length was the same for all considered cases, and it was equal to 3 mm. The results of the analysis demonstrate that, when the laser pulse power density increases, the maximum value of compressive stress increases as well, and tensile stresses occur on the opposite side of the sample. The application of the two-sided laser peening (no overlap) or one-sided peening (50% overlap) can eliminate this effect. An increase in the maximum compressive stress is observed on both sides of the specimen in these cases. Due to an increase in the number of layers in the case of the one-sided peening (no overlap), the maximum compressive stress and penetration depth become greater. However, tensile stresses in the volume of the sample also increase.